Implementation Strategy of Education for Sustainable Development (ESD) in Science Education: A Systematic Literature Review - Zahra Faizah; Diana Rochintaniawati; Nanang Winarno; Rini Solihat (Universitas Syiah Kuala, 2026)
Education is essential to the mission of achieving sustainable future by preparing young generations. The growing adoption of Education for Sustainable Development (ESD) has encouraged increased research on its implementation across educational levels, particularly in science education. This study aims to examine instructional strategies used to implement ESD in science education through a systematic literature review (SLR) guided by the PRISMA framework. A total of 45 articles published between 2016 and 2025 in Scopus-indexed journals were reviewed. The analysis considered key research characteristics, including publication type, year, country, research methodology, educational level, and science content. Notably, the primary emphasis is on assessing the strategies for implementing ESD that have either been enacted or proposed in science education. The findings reveal that ESD is most frequently integrated through general science content, while physics is the least represented discipline. Project-based learning emerges as the most commonly applied instructional strategy overall, whereas school programs and collaborative initiatives are more prevalent in chemistry education. Additionally, a total of 11 other strategies were identified from the literature. This review outlines a comprehensive approach for implementing ESD in science education, serving as a valuable resource for educators aiming to integrate ESD effectively.